Family Guidance for Sakinah: Building Family Harmony Through Islamic Values - Nema Widiantini; Mumu Fahmudin (UIN Sunan Gunung Djati Bandung, 2024)
This study aims to assist families at As-Sa’adah Mosque in Sukasari, Sumedang, in implementing Islamic values to create sakinah, mawaddah, and rahmah families. The research employs the Participatory Action Research (PAR) method, actively involving the community in problem identification, solution design, program implementation, and outcome evaluation. The implemented programs include education, socialization, and hands-on training, such as family counseling, effective communication workshops, Islamic financial management training, and family health classes. The results indicate an increase in spiritual awareness, family management skills, and the strengthening of interpersonal relationships among participants. Evaluations through direct observation and interviews reveal a positive impact on family harmony and a significant contribution to fostering an environment conducive to individual potential development. These findings confirm that a holistic, community-based participatory approach effectively strengthens family resilience and has the potential for wider implementation in other communities. With sustained support from various stakeholders, this program is expected to have a broader impact on improving family quality of life in Indonesia.